Molecular Rare‐Earth‐Metal Hydrides in Non‐Cyclopentadienyl Environments. Issue 6 (20th November 2014) - Fegler, Waldemar; Venugopal, Ajay; Kramer, Mathias; Okuda, Jun
Abstract: Molecular hydrides of the rare‐earth metals play an important role as homogeneous catalysts and as counterparts of solid‐state interstitial hydrides. Structurally well‐characterized non‐metallocene‐type hydride complexes allow the study of elementary reactions that occur at rare‐earth‐metal centers and of catalytic reactions involving bonds between rare‐earth metals and hydrides. In addition to neutral hydrides, cationic derivatives have now become available. Abstract : Beyond Cp : Molecular hydrides of rare‐earth metals play an important role as homogeneous catalysts and as models of solid‐state interstitial hydrides. This Review provides an overview of rare‐earth‐metal hydride complexes(without cyclopentadienyl ligands), with emphasis on the structural motifs and the effect of cationic charges on reactivity.